Semiconductor Nanowires Biosensors for Highly Selective and Multiplexed Detection of Biomolecules - Adam, Tijjani; Mohammed, Aeshah Muhana; Dhahi, Th. S.; Nor Azua, Nur Fatimi; Azizah, N.; Hashim, U.; Gopinath, Subash C.B. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The surface modification of Nano-structure has allowed specific and selective detection to be made on nano structures devices. Current study, a nanowire was surface engineered with the potential of silicon nanowires biosensors (SiO2) which enhance the biosensor activity especially identifying single-stranded bio-molecular such as E.coli DNA. The device’s capabilities were studied based on it response n electrochemical activities of the terminal group of the surface modification agent. NH2 -terminated APTES) to provide rigid chemistry between the DNA organic and Si inorganic link of a biomolecule single_stranded ssDNA probe and SiO2_APTES link nanostructure. Thus, the study demonstrates that silicon nanowire sensing capability to discriminate molecular probe to that of molecule target of supra-genome 21 mers salmonella due to sensitive surface chemistries that made distinguishing the two species. The device captured the molecule precisely; the approach took the advantages of strong binding chemistry created between APTES and biomolecule. The results indicated how modifications of the nanowires provide sensing capability with strong surface chemistries that can lead to specific and selective target detection.